2019
DOI: 10.1111/obr.12883
|View full text |Cite
|
Sign up to set email alerts
|

Changes in patterns of the double burden of undernutrition and overnutrition in Nepal over time

Abstract: Summary Knowledge regarding nutrition transition in Nepal remains limited. This systematic review examined the shifts in undernutrition and overnutrition in Nepal during the past two decades. We searched PubMed for studies and reports published between January 1, 2000, and June 30, 2018. Publications with a sample size greater than or equal to 500 that reported prevalence of nutritional status were included. Six large national reports and 36 studies met study inclusion criteria and were included. Overall, avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In Nepal, a systematic review based on a nationally representative report from 2001 to 2016, showed that the prevalence of stunting, wasting, and underweight among children has declined from 57.2 to 35.8%, 11.2 to 9.7%, and 42.7 to 27.0% respectively. However, overweight and obesity among women has increased from 6.5 to 22.1% over the same period [11]. The prevalence of stunting, wasting, and underweight has declined in the last decade in the context of Nepal [11], however, anemia in children aged under 5 years has been stagnant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nepal, a systematic review based on a nationally representative report from 2001 to 2016, showed that the prevalence of stunting, wasting, and underweight among children has declined from 57.2 to 35.8%, 11.2 to 9.7%, and 42.7 to 27.0% respectively. However, overweight and obesity among women has increased from 6.5 to 22.1% over the same period [11]. The prevalence of stunting, wasting, and underweight has declined in the last decade in the context of Nepal [11], however, anemia in children aged under 5 years has been stagnant.…”
Section: Introductionmentioning
confidence: 99%
“…However, overweight and obesity among women has increased from 6.5 to 22.1% over the same period [11]. The prevalence of stunting, wasting, and underweight has declined in the last decade in the context of Nepal [11], however, anemia in children aged under 5 years has been stagnant. Overweight and obesity has increased in all women acrossall socio-demographic groups [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Tendency to consume calorie-dense food with more saturated fat, trans fat and a sedentary lifestyle results in reproductiveaged women gaining weight [20,29]. In Nepal, the prevalence of overweight/obesity among such populations has increased from an estimated 6.5 % in 2001 to 22.1 % in 2016 [13].…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, a systematic review based on a nationally representative report from 2001 to 2016, showed that the prevalence of stunting, wasting, and underweight among children has declined from 57.2 % to 35.8 %, 11.2 % to 9.7 %, and 42.7 % to 27.0 % respectively. However, overweight and obesity among women has increased from 6.5 % to 22.1 % over the same period [12]. The prevalence of stunting, wasting, and underweight has declined in the last decade in the context of Nepal [13], however, anemia in children aged under five years has been stagnant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation